Capacity Building in Economics : Education and Research in Transition Economies - Pleskovic, Boris (World Bank, Washington, DC, 2013)
The development of the institutional capacity to create and evaluate economic policies remains a critical need-and constraint-in most transition economies if they are to complete the successful passage to fully functioning market economies. To take an active role in the transition process, economic policymakers, business leaders, government officials, and others need a thorough grounding in market-based economics. This requires strengthening economics education and providing support for qualified economists to teach economics at all levels and to carry out high-quality research and policy analysis. Although the education systems in a handful of countries have already risen to the challenge, in many other transition countries, the structure of educational and research institutes remains grounded in the Communist model. This paper presents findings from a comprehensive study assessing the state of economics education and research in 24 countries in East-Central Europe and the former Soviet Union. While 20 countries were initially included because preliminary assessments showed that they lacked the capability to offer high-quality economics education, four additional countries-the Czech Republic, Hungary, Russia, and Ukraine-were included to highlight five centers of excellence that they already host. Based on the experience of these successful centers, the study's findings, and information gathered from a series of donor meetings in Berlin, New York, and Washington, D.C., this paper presents an approach to building new indigenous capacity for teaching and research on market-based economics in regions where the need is particularly critical-the Caucasus, Central Asia, and Southeast Europe.